A Phg2-Adrm1 Pathway Participates in the Nutrient-controlled Developmental Response in Dictyostelium - Cherix, Nathalie (The American Society for Cell Biology, 2006)
Dictyostelium amoebae grow as single cells but upon starvation they initiate multicellular development. Phg2 was characterized previously as a kinase controlling cellular adhesion and the organization of the actin cytoskeleton. Here we report that Phg2 also plays a role during the transition between growth and multicellular development, as evidenced by the fact that phg2 mutant cells can initiate development even in the presence of nutrients. Even at low cell density and in rich medium, phg2 mutant cells express discoidin, one of the earliest predevelopmental markers. Complementation studies indicate that, in addition to the kinase domain, the core region of Phg2 is involved in the initiation of development. In this region, a small domain contiguous with a previously described ras-binding domain was found to interact with the Dictyostelium ortholog of the mammalian adhesion-regulating molecule (ADRM1). In addition, adrm1 knockout cells also exhibit abnormal initiation of development. These results suggest that a Phg2-Adrm1 signaling pathway is involved in the control of the transition from growth to differentiation in Dictyostelium. Phg2 thus plays a dual role in the control of cellular adhesion and initiation of development.